Responses of Aquatic Ecosystems to Environmental Changes in Finland and China - Weckström, Jan; Liao, Mengna; Yu, Ge; Amsinck, Susanne; Kauppila, Tommi; Qin, Boqiang; Zhu, Guangwei; Sarvala, Jouko; Weckström, Kaarina; Tarvainen, Marjo; Kirkkala, Teija; Nurminen, Leena; et al. (Frontiers in Ecology and Evolution, 2015)
The concern for the state of global freshwater reservoirs has increased due to deterioration of the water quality during the last decades. This has prompted monitoring and restoration efforts such as the European Water Framework Directive and the national-scale 2nd-investigation and monitoring of the water quality, water volume and biota resources in China. The challenge so far has been the determination of the “natural” state (reference conditions) of freshwater ecosystems. We used the sediment archives of five lakes and one brackish water embayment in Finland and China to assess the impact of selected variables of climatology, hydrology, nutrients, and changes in human population on these ecosystems during the last few centuries. The study sites represent catchment areas with varying land use. Despite the long distance between the sites and their different land-use characteristics, the direction and timing of changes during the last few centuries are well comparable between the high latitudes of Finland and the mid-low latitudes of China. This study reinforces the sensitivity of aquatic ecosystems to environmental change and underlines the usefulness of the palaeolimnological approach as a tool for determining reference conditions.